De Quervain disease in volleyball players - Rossi, C.; Cellocco, P.; Margaritondo, E.; Bizzarri, F.; Costanzo, G. (The American Journal of Sports Medicine, 2005)
Background: Chronic inflammatory tendon diseases in athletes are frequent, and they often result from modifications in normal kinematics of a tendon associated with a patient`s anatomical determinants. De Quervain stenosing tenosynovitis is an inflammatory disease of tendons of the first dorsal compartment of the wrist. There is no literature about this disease concerning professional volleyball players.